2006
DOI: 10.1007/s10457-005-8846-z
|View full text |Cite
|
Sign up to set email alerts
|

Farm Level Tree Planting in Pakistan: The Role of Farmers’ Perceptions and Attitudes

Abstract: The low proportion of forested land and continuing degradation of existing forest cover are serious threats to the sustainability of forestry in Pakistan. Farm forestry has been identified as a feasible solution, particularly in the plain areas. Applying the Theory of Planned Behaviour in a survey of 124 farmers in Dera Ismail Khan district of Pakistan's North West Frontier Province showed that farmers' willingness to grow trees on their farms is a function of their attitudes towards the advantages and disadva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 10 publications
11
66
3
1
Order By: Relevance
“…This is particularly critical for less experienced tree planters who may underestimate the level of difficulty or work involved, which is especially relevant for those that are quite aged. Reasons why landowners in our study (particularly full-time farmers) would opt out of schemes accord with other studies, particularly if livelihoods would be affected by having native species on farms, such as loss of tenure and negative perceptions of biodiversity (Zubair & Garforth, 2006). More recent studies have also indicated that uptake of assetbuilding PES initiatives depends more on landowner attitudes and perceptions of how such policies affect future livelihoods (Trevisan et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…This is particularly critical for less experienced tree planters who may underestimate the level of difficulty or work involved, which is especially relevant for those that are quite aged. Reasons why landowners in our study (particularly full-time farmers) would opt out of schemes accord with other studies, particularly if livelihoods would be affected by having native species on farms, such as loss of tenure and negative perceptions of biodiversity (Zubair & Garforth, 2006). More recent studies have also indicated that uptake of assetbuilding PES initiatives depends more on landowner attitudes and perceptions of how such policies affect future livelihoods (Trevisan et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…These examples are described here and explore the perceptions farmers have about certain agroforestry practices, their impact and management (Douthwaite et al 2002, Mekoya et al 2008, Sileshi et al 2008b). There are a few more examples of studies outside of sub-Saharan Africa which set out to measure attitudes towards agroforestry and the environment and link these to the decision to adopt (Sood and Mitchell 2004, Zubair and Garforth 2006, McGinty et al 2008; however, these are not discussed here as they are beyond the scope of this paper.…”
Section: Studies Focusing On Intrinsic Factorsmentioning
confidence: 99%
“…Willock et al, 1999;Burton, 2004). Examples of this approach are related to the application of the Theory of Reasoned Action and the Theory of Planned Behaviour (Ajzen, 1991;Fishbein and Ajzen, 1975;Burton, 2004) to pesticide use (Heong and Escalada, 1999) and to agro-forestry practices (Zubair and Garforth, 2006).…”
Section: Behavioural Theorymentioning
confidence: 99%
“…Heong and Escalada, 1999;Heong et al, 2002), the social context (e.g. Nkamleu and Adesina, 2002), imitation of peers (Schmit and Rounsevell, 2006), attitudes and perceptions (Zubair and Garforth, 2006) and the role of specific contingencies which might influence farmers in an action context, e.g. inadequate risk communication (e.g.…”
Section: Integrative Approachmentioning
confidence: 99%